Endogeneity in threshold nonlinearity tests - Dentler, Alexander (2014)
This article shows the conditions under which endogeneity of a regressor variable does not affect threshold nonlinearity tests. Inference on the values of the parameters derived from standard statistics is also appropriate. Simulation techniques are used to approximate the p-value of the test. Monte Carlo simulations confirm the validity of Wald tests in the presence of endogeneity in the regressors.